2017
DOI: 10.5334/gjgl.95
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study on the processing of long-distance wh-movement in a second language

Abstract: Recent behavioural evidence from second language (L2) learners has suggested native-like processing of syntactic structures, such as long-distance wh-dependencies in L2. The underlying processes are still largely debated, while the available neuroimaging evidence has been restricted to native (L1) processing. Here we test highly proficient L2 learners of English in an fMRI experiment incorporating a sentence reading task with long-distance wh-dependencies, including abstract syntactic categories (empty traces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 55 publications
2
7
0
1
Order By: Relevance
“…The prime area activated at the frontal brain region was the MFG, while for the MTG and STG, activation was at the temporal brain region. This finding is in line with previous researches where they also found the activation of the frontal and temporal region during the processing of English (Pliatsikas et al, 2017), Mandarin (Bulut et al, 2018), Chinese (Xuan et al, 2020a, and the Austrian sign language's relative clause (Krebs et al, 2018). Processing non-canonical structures like SRC and ORC requires the extensive roles of the frontal and temporal brain regions.…”
Section: The Differences In Functional Neural Activation Of Malay Lan...supporting
confidence: 92%
See 1 more Smart Citation
“…The prime area activated at the frontal brain region was the MFG, while for the MTG and STG, activation was at the temporal brain region. This finding is in line with previous researches where they also found the activation of the frontal and temporal region during the processing of English (Pliatsikas et al, 2017), Mandarin (Bulut et al, 2018), Chinese (Xuan et al, 2020a, and the Austrian sign language's relative clause (Krebs et al, 2018). Processing non-canonical structures like SRC and ORC requires the extensive roles of the frontal and temporal brain regions.…”
Section: The Differences In Functional Neural Activation Of Malay Lan...supporting
confidence: 92%
“…Therefore, we postulated that the Malay SRC was easier to comprehend than ORC by L1 and L2. The current finding has concurred with the previous research in the language which has SVO word order such as English (Pliatsikas et al, 2017), and language that has free word order such as Basque (Arantzeta et al, 2017) and German (Harding et al, 2019).…”
Section: Comprehension Ability Of Malay Language Relative Clause Amon...supporting
confidence: 90%
“…Further, regarding contact with the L2, it has been proposed that even if exposure commences outside of a particular sensitive period, "increased exposure may well lead to the increased automatization or entrenchment of grammatical processing routines" (Clahsen & Felser, 2017, p. 6). Recent findings suggest a correlation between exposure and processing nativelikeness: specifically, naturalistic L2 exposure seems to play a decisive role in engendering more syntactically rather than semantically driven L2 processing (Pliatsikas, Johnstone, & Marinis, 2017;Pliatsikas & Marinis, 2013). In light of these findings, it is plausible that early L2 acquirers who have received considerable naturalistic L2 exposure would show more nativelike garden-path processing.…”
Section: L1 and L2 Processing Of Object-subject Ambiguitiesmentioning
confidence: 99%
“…Classroom L2 learners seem to process sentences of the form in (1a) and (1b) identically, which has led to the suggestion that they do not make use of the clause boundary when processing dependencies of this type (Marinis et al, 2005; Pliatsikas and Marinis, 2013; Pliatsikas et al, 2017; although, for different findings in the auditory modality, see Fernandez et al, 2018). This seems to hold even when the classroom learners have relatively high levels of proficiency, as was the case in Marinis et al (2005) and Pliatsikas et al (2017). Consequently, it has been suggested that high L2 proficiency alone is not sufficient to engender use of the intermediate gap (Pliatsikas and Marinis, 2013: 180).…”
Section: Introductionmentioning
confidence: 99%
“…One factor that has been found to influence the L2 processing of long-distance wh-dependencies is naturalistic L2 exposure, where a facilitative effect of the clause boundary has been identified among L2 speakers who have spent time in L2 immersion contexts (Pliatsikas and Marinis, 2013; Pliatsikas et al, 2017). This result has been attributed to increased proceduralization of grammatical knowledge brought about by extensive L2 exposure, in line with an account in which L2 grammatical processing becomes more automatic as L2 proficiency and exposure increase (see, for example, Ullman, 2001).…”
Section: Introductionmentioning
confidence: 99%